Stress-strain state of proximal femur after joint arthoroplasty with neck defect conditions at the minor trochanter level with different stem types - Filipenko, Volodymyr; Bondarenko, Stanislav; Volodymyr, Tankut; Zhygun, Anatoliy; Yaresko, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
In the primary hip arthroplasty, the metaphyseal fixation type stems have proved to be very useful, allowing the stability of the fixation and the diaphyseal section of the femur to remain stable for future revision surgeries. However, with the increase in the defect of bone tissue as a result of trauma, it becomes necessary to use the stems of a second type of fixation. Purpose: to investigate the stress-strain distribution of the proximal femur in conditions of arthroplasty with stems of various types of fixation in case of defect of the femoral neck at the level of a minor trochanter. Methods: using the finite element method, the pelvic and hip joints were modeled in various phases of walking. The model included the endoprosthesis «Zimmer» installed in the left hip joint in two versions — with metaphyseal and diaphyseal stems fixation types. Results: stress-strain distribution of the proximal femur in conditions of endoprosthetics with a femoral neck defect at the level of a minor trochanter was different for variants of the model with diaphyseal and metaphyseal stem fixation in all phases of the movement. The stress-strain data for the version of the model with the metaphysical fixation stem almost always exceeded the values obtained with the diaphysial type of fixation. The greatest difference was found for the first and third phases of movement in the upper third of the medial surface of the femur at the site of contact with the endoprosthesis. <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Conclusions:<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> in the case of a femoral neck defect at the level of a minor trochanter in conditions of endoprosthetics, it is necessary to give preference to the use of an endoprosthesis with a diaphysial fixation stem.